The Effect of Transactional Leadership and Transformational Leadership on Employees Creativity - Wilson Bogar (AIBPM Publisher, 2019)
The purpose of this study is to analyze and explain the effect of transactional leadership and transformational leadership on employees creativity at Secretarial of SITARO Regency. This researh is explanatory research. Samples taken by proportional random sampling technique and sample size are 40 out of 66 Sitaro Regency Secretarial’s employees. Data collecting technique is questionnaire and data analysis is regression analysis. The result of this study showed that transactional leadership and transformational leadership have simultaneously affect on employee’s creativity. Transactional leadership has negatively affected on employee’s creativity, but the other one (transformational leadership) has positively affect on employee’s creativity Keywords: employee creativity, transactional leadership, transformational leadership